Peran Asrama Salsabila dalam Mengembangkan Kemampuan Tahfiz dan Pemahaman Tafsir Al-Qur’an bagi Mahasantriwati - Sri Ahadah Nuril Fajar; Ahmad Zuhri (CV Global Research Publication, 2026)
This study examines the role of Salsabila Dormitory in developing Qur’anic memorization ability and understanding of Qur’anic interpretation among female students. This research is based on the importance of integrating memorization and interpretation so that students’ interaction with the Qur’an does not stop at recitation and memorization, but also leads to understanding, internalization, and practice of Qur’anic values in daily life. This study aims to identify the role of Salsabila Dormitory in developing female students’ Qur’anic memorization ability and understanding of Qur’anic interpretation. This research used a qualitative field method with a phenomenological approach. The research subjects consisted of a dormitory supervisor, an administrator, and a female student who were selected purposively because they were directly involved in Qur’anic memorization and interpretation activities. Data were collected through observation, in-depth interviews, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing, while data validity was maintained through source and technique triangulation. The findings show that Salsabila Dormitory plays an important role in building a Qur’anic culture through regular memorization, muraja’ah, tafsir studies, Arabic language learning, and congregational worship guidance. These programs strengthen students’ memorization, understanding, appreciation, and practice of Qur’anic values. This finding is significant because it shows that dormitory-based Qur’anic education can become an integrative model for connecting memorization, interpretation, and religious character formation among female students.